< a > Prismatic, < a > basal, and < c plus a > slip strengths of commercially pure Zr by micro-cantilever tests - Gong, J; Britton, T; Cuddihy, M; Dunne, F; Wilkinson, A (Elsevier, 2015)
Slip strengths of 〈a〉 basal, 〈a〉 prism, and 〈c+a〉 pyramidal systems in commercially pure zirconium have been determined using micro-cantilever testing. A range of single crystal cantilevers 0.5 μm to 10 μm wide, oriented for single slip were prepared using focused ion beam (FIB) machining and subsequently deflected using a nanoindenter. The critical resolved shear stress (τcrss) was found by fitting a crystal plasticity finite element model to the experimental load–displacement data for these micro-bending tests. All the three slip systems in α-Zr show a marked size effect in bending described well by τCRSS(W) = τ0 + AWn, where W is the cantilever width, τ0 is the CRSS at the macro scale and n = ∼−1. The exponent, n, of near −1 is in good accord with hardening caused by the back stress generated by dislocations piling up at a diffuse barrier caused by the reduction of stress near the neutral axis. The macro scale CRSS values were used to successfully simulate deformation of a conventional macroscopic compression test.